Nanotechnology in Agricultural Diseases and Food Safety - and Rohit Kumar2, Madhuri Sharon1*, Ajoy Kr. Choudhary2 (Journal of Phytology, 2010)
SUMMARY Nanotechnology can be used for combating the plant diseases either by controlled delivery of functional molecules or as diagnostic tool for disease detection. Nanotechnology, nano particles and quantum dots (QD) have emerged as pivotal tool for detection of a particular biological marker with extreme accuracy. The possibilities in future as well as some success that have been achieved so far are discussed in this review. Diagnosis of a disease in its very early stage can play important role in treatment. Due to phenomenal advancement in nanotechnology, QDs have emerged as pivotal tool for detection of a particular biological marker with extreme accuracy. QDS being very photo-stable and optically sensitive can be used as labeling and can be easily traced with ordinary equipment. Early detection of tumor markers using quantum dots is proved to be boon for cancer diagnosis. Use of QDs has also helped in unlocking complex neurological phenomenon, such as molecular activities at synapse during neurotransmission. QDs also give important information about receptor movement if tagged with suitable antibodies. In short, optical stability and easy to handle properties have made QDs to remain at the apex of medical diagnostics. Key words: Nanotechnology, Nanoparticles, Quantum dots, Nano-carbon, Carbon Nanotubes, Nano silver, Nano Alumino-silicate, Nano-sensors, Nano-emulsion <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Madhuri Sharon et al. Nanotechnology in Agricultural Diseases and Food Safety. Â J Phytol 2/4 (2010) 83-92.